2007
DOI: 10.1073/pnas.0705553104
|View full text |Cite
|
Sign up to set email alerts
|

Identification of xanthurenic acid 8- O -β- d -glucoside and xanthurenic acid 8- O -sulfate as human natriuretic hormones

Abstract: showed that when these two variables were controlled, the kidney was still able to increase sodium excretion in response to a salt load. Several lines of evidence argued for a small-molecule signal as a definitive modulator of sodium excretion by the kidney. However, the chemical nature of the suspected natriuretic agent remained unknown. Here we report the identification and natriuretic activity of two closely related small molecules isolated from human urine, xanthurenic acid 8-O-␤-D-glucoside and xanthureni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
29
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 25 publications
4
29
1
Order By: Relevance
“…3A). However, the addition of xanthministered xanthurenic acid intravenously as a bolus injection and an infusion to rats, because a detailed method is not described in the report by Cain et al (1). As a result, we observed the diuresis by the xanthurenic acid infusion.…”
supporting
confidence: 47%
See 1 more Smart Citation
“…3A). However, the addition of xanthministered xanthurenic acid intravenously as a bolus injection and an infusion to rats, because a detailed method is not described in the report by Cain et al (1). As a result, we observed the diuresis by the xanthurenic acid infusion.…”
supporting
confidence: 47%
“…Cain et al failed to obtain the diuresis by the xanthurenic acid administration in rats (1), and this is the first report showing the diuresis in rats administered with xanthurenic acid. They did not describe the dosage in the report (1), and their dosage might be lower than our dosage. In addition, their infusion was via the artery, but our administration was from the vein.…”
mentioning
confidence: 99%
“…In fact, 4-hydroxyl moiety of XA molecule is in a para-position to the nitrogen atom and has weak phenolic properties, suggesting that it seems unlikely to be sulfated. The nuclear magnetic resonance spectroscopic analyses of XA sulfate that was recently purified from urine also clearly demonstrated the sulfoconjugation occurred at 8-hydroxyl position (Cain et al, 2007). at ASPET Journals on May 11, 2018 jpet.aspetjournals.org…”
Section: Discussionmentioning
confidence: 96%
“…4,5) Cain et al reported that 8-O--D-glucoside and 8-O-sulfate of xanthurenic acid caused natriuresis in rats. 28) Sulfation of xanthurenic acid occurred in various tissues including the liver, stomach, jejunum, colon, and kidney, and sulfotransferase SULT1C2 was exhibited to be predominantly expressed in the proximal tubule, where OAT1 and OAT3 work. 29,30) Accordingly, it is intriguing whether the formation of xanthurenic acid sulfate followed by its tubular uptake by OAT1 and OAT3 is responsible for diuresis.…”
Section: Discussionmentioning
confidence: 99%